2016
DOI: 10.1183/13993003.00057-2016
|View full text |Cite
|
Sign up to set email alerts
|

Variation in vitamin D deficiency among tuberculosis patients by ethnic group and geographical region of birth: evidence from a diverse south London population

Abstract: Comparison of effectiveness and safety of imipenem/clavulanate-versus meropenem/clavulanate-containing regimens in the treatment of multidrug and extensively drug-resistant tuberculosis. Eur Respir J 2016; 47: 1758-1766. 9 Tiberi S, Sotgiu G, D'Ambrosio L, et al. Effectiveness and safety of imipenem-clavulanate added to an optimized background regimen (OBR) versus OBR control regimens in the treatment of multidrug-resistant and extensively drug-resistant tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The question arises of why then is there a variation in vitamin D status if they are from a homogenous social setting? Genetic susceptibility to vitamin D deficiency has been suggested by Pilarski et al, 9 and Sita-Lumsden et al 18 The genetic variation may explain our finding. We advocate further exploration of this observation.…”
Section: Discussionsupporting
confidence: 61%
“…The question arises of why then is there a variation in vitamin D status if they are from a homogenous social setting? Genetic susceptibility to vitamin D deficiency has been suggested by Pilarski et al, 9 and Sita-Lumsden et al 18 The genetic variation may explain our finding. We advocate further exploration of this observation.…”
Section: Discussionsupporting
confidence: 61%
“…The number of subjects experiencing the outcome of interest in previous studies was limited, however, ranging from 3 to 18 over follow-up periods 2 to 4 years. These studies have been found to vary with study design, geographical location 8 , as well as ethnicities 30 and gender 24 of subjects. Thus, studies with larger sample sizes in different populations are needed to help clarify whether the association between vitamin D and susceptibility to TB infection or disease is causal in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Having dark skin when living permanently at northern latitudes would have caused vitamin D 3 deficiency, resulting in reduced bone strength and a defective immune system. For example, nowadays, the tuberculosis rate of individuals with dark skin living distant from the equator is significantly higher than that of people with light skin [20].…”
Section: Vitamin D and Human Genetic Adaptationmentioning
confidence: 99%